Role of CMV & Interferon-? in Myocardial Infarction, Angina and Hypertension - Haider, Mehvash; Rizvi, Meher; Malik, Abida; Azam, Md; Rabbani, M U (Bangladesh Journal of Medical Science, 2015)
Aims: There is limited epidemiologic evidence relating CMV specifically to primary coronary atherosclerosis. Its association with atherosclerosis and restenosis appears to have merit and needs to be studied further. Cardiovascular disease being an inflammatory process leads to detectable rise in inflammatory markers like Interferon-?. The aim of this study was to evaluate the role of CMV and Interferon-? in cardiovascular disease. Methods: Study was conducted on 63 randomly selected cardiovascular disease patients and 29 healthy controls. ELISA for detection of IgG antibodies against CMV were detected (Calbiotech Diagnostics, USA). Interferon-? levels were determined by ELISA (Diaclone, USA). Relevant investigations, clinical history & examination were recorded. Results: Of 63 cases 41 (65.08%) were positive for IgG antibodies against CMV and 8 (27.58%) of 29 controls were IgG positive (p<0.001). Among CMV seropositives 19 (46.34%) were MI patients, 13 (31.70%) were hypertensives and 9 (21.95%) were angina patients. The mean value of Interferon-? for cases was 32.13pg/ml, the mean of controls was 11.32pg/ml (p<0.0001). Among CMV IgG seropositives the mean value of Interferon-? in hypertensives was 12.76pg/ml, in angina patients was 32.48pg/ml and in MI patients was 67.10pg/ml. Conclusion: In our study CMV seropositivity was significantly associated with CVD cases. CMV seropositivity increased with severity of disease. Mean value of Interferon-? was higher among cases reflecting role of inflammatory aetiology in CVD. Mean value of Interferon-? increased with severity of disease infection clearly indicating the role of inflammatory markers along with CMV in cardiovascular disease. Bangladesh Journal of Medical Science Vol.14(4) 2015 p.339-345